Penerapan Learning Cycle 5E menggunakan LKS berbantuan AR dalam Optimalisasi Manajemen Pembelajaran PAI - Calam, Ahmad; Mardianto, Mardianto; Nadawina, Nadia; Irwan, Irwan (Journal of Instructional and Development Researches, 2025)
This study aims to explore the implementation of the Learning Cycle 5E (LC5E) instructional model supported by Augmented Reality (AR)-based Student Worksheets (LKS) in Islamic Religious Education (PAI) learning at SMP PAB 19 Manunggal, Deli Serdang Regency. Employing a descriptive qualitative approach, data were collected through in-depth interviews, participatory observations, and documentation, and were analyzed using NVIVO 12 Plus software. This approach demonstrates significant potential in enhancing the quality of PAI learning that is responsive to technological developments and the needs of the digital generation. The findings reveal that the integration of AR in each phase of the 5E model enhances student engagement, reinforces understanding of religious concepts, and facilitates more interactive and meaningful learning experiences. Thematic analysis identified the key benefits of AR, including improved visualization of abstract concepts, increased learning motivation, and ease in practicing religious rituals. However, challenges such as limited device availability and the need for teacher training were also identified. The results of this study indicate that the average religious communication ability of the class using Learning Cycle 5E is 80, while the average class using PBL practice is 72. Statistically, the average religious communication ability of students in learning practice is higher than students in PBL. Students' religious communication skills in Learning Cycle 5E using LKS assisted by Augmented Reality achieved classical completeness with a completeness level of 91%.